Geochemistry and solute fluxes of volcano-hydrothermal systems of Shiashkotan, Kuril Islands - Kalacheva Elena; Taran Yuri; Kotenko Tatiana (My University, 2015)
Shiashkotan Island belongs to the Northern Kuril island arc and consists of two joined volcanoes, Sinarka and Kuntomintar, with about 18 km of distance between the summits. Both volcanoes are active, with historic eruptions, and both emit fumarolic gases. Sinarka volcano is degassing through the extrusive domewith inaccessible strong and hot (N400 °C) fumaroles. A large fumarolic field of the Kuntomintar volcano situated in a wide eroded caldera-like crater hosts many fumarolic vents with temperatures from boiling point to 480 °C. Both volcanoes are characterized by intense hydrothermal activity discharging acid SO4-Cl waters, which are drained to the Sea of Okhotsk by streams. At least 4 groups of near-neutral Na-Mg-Ca-Cl-SO4 springs with temperatures in the range of 50–80 °C are located at the sea level,within tide zones and discharge slightly altered diluted seawater. Volcanic gas of Kuntomintar as well as all types of hydrothermal manifestations of both volcanoes were collected and analyzed for major and trace elements and water isotopes. Volcanic gases are typical for arc volcanoes with 3He/4He corrected for air contamination up to 6.4 Ra (Ra=1.4 ×10−6, the air ratio) and δ13C (CO2) within −10‰to−8‰VPDB. Using a saturation indices approach it is shown that acid volcanic waters are formed at a shallow level, whereas waters of the coastal springs are partially equilibrated with rocks at ~180 °C. Trace element distribution and concentrations and the total REE depend on the water type, acidity and Al+Fe concentration. The REE pattern for acidic waters is unusual but similar to that found in some acidic crater lake waters. The total hydrothermal discharge of Cl and S from the island associated with volcanic activity is estimated at ca. 20 t/d and 40 t/d, respectively, based on the measurements of flow rates of the draining streams and their chemistry. The chemical erosion of the island by surface and thermal waters is estimated at 27 and 140 ton/km2/year, respectively, which is 2–3 times lower than chemical erosion of tropical volcanic islands.
Keywords: 38.33.17 Геохимия природных процессов; Кунтоминтар; Синарка; Shiashkotan, Kuril Islands; He-C-H-O isotopes